Les karsts de l’Est canadien - Corbel, Jean (Cahiers de géographie du Québec, 1958)
This is a systematic study of karsts in Eastern Canada especially caves and underground streams. The analysis of the limestone content in the water bas been used to study the actual dissolution of limestone. It bas been deducted that some of the most typical caves, such as the Saint-Casimir cave in Portneuf county, was formed 3,500-4,000 years ago. This dating is cross-examined with other factors supplied by the physical geography of the area : ice retreat, study of pollens, C.14 analysis, post-glacial surrection, etc.The evolution of the limestone coast of the Mingan-Anticosti area is also described. Everywhere, in the Mingan area and the Anticosti region as well as in the Saint-Casimir cave, the erosion is very rapid. It is a constant fact in regions with heavy snowfalls as demonstrated in similar regions of Norway and Alaska.The climatic influence on the shape and speed of karstification is a determinant factor.